The effect of listening to al-Quran recitation on mood among Muslim patients attending primary care clinic at Hospital Universiti Sains Malaysia - Norwati, Daud; Juwita, S; Mujahid, B (2016)
Introduction: Studies have shown that reading and listening to The Quran relieve stress and provide a relaxing body response. The verses of Al-Quran are being used by Muslims in many activities in their life. The objectives of this study was to determine the effect of listening to The Quran on mood score using POMS-B (Profile of Mood State-Brief) among Muslim patients attending the Primary Care Clinic at Hospital Universiti Sains Malaysia. Methods: This was a randomized controlled trial of 202 patients who were randomly allocated to either listening to Al-Quran recitation group or control group. At baseline and thirty minutes after the intervention, mood score using POMS-B (Profile of Mood State-Brief) were assessed. There were six measured domains in POMS-B which were tension, depression, anger, confusion, fatigue, and vigour activity. It also measured total mood disturbance. Results: The change for total mood disturbance score for pre and post intervention was 4.05 (95% CI: 3.4, 4.7) in the intervention group and 2.63 (95% CI: 1.7, 3.5) in the control group. The difference was statistically significant (P=0.001). Other domains which showed statistically significant difference between the intervention and control group were tension, anger, fatigue, and rigour. The difference in the domains of depression and confusion were not statistically significant Conclusion: This study showed that listening to Al-Quran recitation could result in improvement in most areas affecting mood. This method may be used in the management of Muslim patients with mood disorders such as anxiety as well as other mental health issues.